Excellence Available Everywhere: The Virtual Pathology Grand Rounds Experience. Issue 5 (12th May 2021) - Mirza, Kamran M; Gonzalez, Raul S; Jiang, Xiaoyin "Sara"; Khanafshar, Elham; Wobker, Sara E
Abstract: Objectives: The goal is to describe the use of a virtual platform in the delivery of Virtual Pathology Grand Rounds (VPGR) and discuss the overall experience from the perspective of hosts, speakers, and participants. Methods: Zoom was a natural choice for an online format because virtual platforms had been increasingly used to conduct meetings and medical education. VPGR hosted 14 speakers on a variety of topics, including subspecialty anatomic pathology material, digital pathology, molecular pathology, and medical education. Results: There were 221 registrants and 114 participants for the first lecture, reaching a maximum of 1, 268 registrants for the 12th lecture and the maximum limit of 300 participants during 3 lectures. Speakers stated that VPGR conveniently provided career-building opportunities through partnerships with host universities and remote attendance. Participants identified a lack of interpersonal communication and technical challenges as downsides. Conclusions: VPGR serves as strong proof of concept for the feasibility and demand for high-quality, remote academic pathology talks.